2016
DOI: 10.1080/13880209.2016.1185633
|View full text |Cite
|
Sign up to set email alerts
|

The protective potential of metformin against acetaminophen-induced hepatotoxicity in BALB/C mice

Abstract: The results suggest metformin protects hepatocytes against acute acetaminophen toxicity. Metformin is indicated to diminish oxidative stress, proinflammatory cytokines, and hepatocyte necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…It is worth noting, however, that metformin is not intrinsically hepatotoxic and can be safely administered even in the context of mildly abnormal transaminases[ 137 ]. In fact, animal studies have revealed a protective potential of metformin against acetaminophen-induced hepatotoxicity[ 138 , 139 ]. Additionally, MALA is an exceedingly rare condition with an estimated incidence of < 10 per 100000 patient-years of exposure in patients without significant renal impairment[ 140 ].…”
Section: Management Of Diabetes In Patients With Liver Diseasesmentioning
confidence: 99%
“…It is worth noting, however, that metformin is not intrinsically hepatotoxic and can be safely administered even in the context of mildly abnormal transaminases[ 137 ]. In fact, animal studies have revealed a protective potential of metformin against acetaminophen-induced hepatotoxicity[ 138 , 139 ]. Additionally, MALA is an exceedingly rare condition with an estimated incidence of < 10 per 100000 patient-years of exposure in patients without significant renal impairment[ 140 ].…”
Section: Management Of Diabetes In Patients With Liver Diseasesmentioning
confidence: 99%
“…These findings go in hand with Galal et al, [16] and Somanawat et al, [26] who reported that APAP caused a significant decrease in liver GSH and GPx activity which paralleled the increase in MDA levels and with Alipour et al, [28] who detected increased tissue levels of lipid peroxidation products with decreases in hepatic levels of reduced GSH, GSH peroxidase and reductase. Recently, Ding et al, [4] reported disturbed hepatic tissue antioxidant activities with increasing hepatic MDA contents and reducing hepatic tissue SOD, GSH-PX and GSH activity, Saeedi Saravi et al, [33] also reported that oral APAP decreased GSH and SOD activities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, metformin can potentially reduce adverse cardiac remodeling in hypertensive heart disease (41). Saeedi et al also demonstrated that metformin inhibited inflammatory cytokines, oxidative stress and necrosis by acetaminophen-induced hepatotoxicity in mice through hepatocytes protection and an antiinflammation and antioxidative mechanism (42). There is clear evidence that metformin can decrease cell death in cerebral ischemia (43).…”
Section: The Novel Beneficial Effectsmentioning
confidence: 99%